2009
DOI: 10.1111/j.1365-2990.2008.01006.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the translocator protein of 18 kDa by microglia, macrophages and astrocytes based on immunohistochemical localization in abnormal human brain

Abstract: Aims: Microglia are involved in neurodegeneration, are prime targets for anti‐inflammatory therapy and are potential biomarkers of disease progression. For example, positron emission tomography imaging employing radioligands for the mitochondrial translocator protein of 18 kDa (TSPO, formerly known as the peripheral benzodiazepine receptor) is being scrutinized to detect neuroinflammation in various diseases. TSPO is presumably present in activated microglia, but may be present in other neural cells. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
330
1
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 409 publications
(361 citation statements)
references
References 69 publications
(136 reference statements)
23
330
1
5
Order By: Relevance
“…1 Therefore, TSPO has become a target for positron emission tomography (PET) radioligands used to quantify the activation and density of these cells in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…1 Therefore, TSPO has become a target for positron emission tomography (PET) radioligands used to quantify the activation and density of these cells in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…This fact has previously been used to validate TSPO tracers in healthy animals (10). Previously, it has been reported that the TSPO protein is also expressed in the ependymal cells (34) and cells within the choroid plexus (9,35). Additionally, the binding in the olfactory bulbs in rodents has previously been observed (36).…”
Section: Discussionmentioning
confidence: 99%
“…38 Briefly, sections were treated with Target Retrieval Solution (Dako, Carpinteria, CA) for antigen retrieval and then with rabbit anti-HO-1 antibody (Stressgen) at 1:200 for 2 hours at room temperature. ImmPRESS anti-rabbit Ig peroxidase kit (Vector Laboratories Ltd., Burlingame, CA) in combination with diaminobenzidine was used to develop a brown reaction product.…”
Section: Ho-1 Ihc and Immunofluorescencementioning
confidence: 99%